Optimization of Sustainable Goat Farm Productivity Improvement through Complete Feed Introduction Technology in Kaliploso Village, Banyuwangi - Saputro, Amung Logam; Agustono, Bodhi; Prastiya, Ragil Angga; Mumtazi, Fauzan; Tito, Muhammad (Universitas Airlangga, 2023)
Increasing the level of the community economy through the livestock sector is increasingly in demand. The livestock sector is experiencing an increase in interest in one of them is goat farming. Not much different from the success factor of increasing the productivity of livestock, the success of goat livestock is also influenced by several factors including genetics, feed, and maintenance management. The role of farmers is necessary to achieve the desired level of productivity success. Breeders in the group Banyuwangi Goat Breeder must be prepared to be a breeder who is aware of the mechanism of raising a good right. Therefore, the education of farmers to be related to the way or technique of raising goats is good and right, goat cultivation management in the form of types of goats, goat reproduction, goat health to the manufacture of complete feed that is right must be understood by farmers. The purpose of this activity is to improve farmers ' understanding of the importance of understanding the basic aspects of breeding including genetic, feed, and maintenance management. In addition to aiming to improve farmers ' understanding of goat breeding techniques, this extension is expected to also be a solution in solving economic and social problems, especially in the field of goat farming, and independently farmers can make complete feed independently. However, the sustainability of coaching is expected to improve the quality of farmers in raising livestock and as a mechanism for evaluating the complete feed until the formation of a commercial and viable complete feed. Feed model as a source of livestock nutrition.